Doctorate Degrees Earned by Early Canadian Geologists - Middleton, Gerard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2003)
Summary The first doctorate degrees in the geological sciences earned by Canadians were: Ph.D., Yale, 1871 by Bernard J.Harrington; Ph.D., Gôttingen, 1877 byJoseph William Winthrop Spencer;Ph.D., Breslau, 1882 by Arthur P.Coleman; Ph.D., Johns Hopkins, 1888by Andrew C. Lawson; Ph.D., Heidelberg, 1892 by Frank Dawson Adams; and Ph.D., Toronto, 1900 by William A. Parks. McGill and the Geological Survey of Canada were the two institutions that most encouraged Canadians to seek graduate-level qualifications. Yale had an important influence on McGill: its SheffieldScientific School influenced William Dawson to set up the McGill Department of Practical Science, and he appointed Harrington to be its head. In the 1860s and 1870s, the Yale school was the preeminent school in the United States for advanced study in geology and mineralogy, and the professors there encouraged many of their students to continue their studies in Germany: this advice was then taken up by McGill graduates, notably Spencer and Adams.By the 1890s graduate studies in geology had been developed to the doctorate level in many other American universities, so that travel to Germany was no longer necessary.